A study on the current status of home-based pulmonary rehabilitation in stable chronic obstructive pulmonary disease patients and its impact on quality of life (稳定期慢性阻塞性肺疾病患者居家肺康复现状及其对生活质量影响的调查研究) - WANG Tao (王涛); YAN Qiaoyuan (颜巧元); WU Hongyan (吴红艳); YANG Hualu (杨华露); ZHOU Juan (周娟); MO Beirong (莫蓓蓉); LIU Xianliang (刘贤亮) (Association of Integrative Nursing, 2024)
Objective To investigate the home-based pulmonary rehabilitation training and self-management practices among patients with chronic obstructive pulmonary disease (COPD) and assess the impact of these practices on their quality of life. Methods Convenience sampling was used to select 81 patients with COPD as research subjects, and a questionnaire was administered using the "Questionnaire Star" platform. The primary investigation focused on patients' self-management and pulmonary rehabilitation training at home, as well as the influence of self-management and home-based pulmonary rehabilitation on patients' quality of life. Results Among the 81 respondents, 46. 91%(38/81) of patients adhered to respiratory exercises (more than 3 days per week), 61. 73%(50/81) of patients were able to maintain regular physical exercises (more than 3 days per week), 75. 31%(61/81) of patients followed their medication prescriptions as advised by their doctors, and 64. 20%(52/81) of patients did not receive home oxygen therapy. The COPD Assessment Test score was (20. 22 ±7 . 48), which indicated a moderate level of quality of life among COPD patients. Factors such as age, education level, duration of illness, employment status, the number of hospitalizations due to COPD, alcohol and smoking habits, attempts to quit smoking, adherence to medication prescriptions, home oxygen therapy, duration of continuous oxygen therapy, and the number of days of respiratory and exercise training per week were found to have a significant impact on the quality of life(P＜0. 01). The patents' quality of life was associated with frequency of alcohol consumption, smoking habits, attempts to quit smoking, adherence to medication prescriptions, home oxygen therapy, duration of continuous oxygen therapy and number of days of respiratory training per week(P＜0. 01). Conclusion Home-based pulmonary rehabilitation helps improve self-management abilities among patients with COPD, encourages the adoption of healthy lifestyle habits, and promotes adherence to scientifically guided home oxygen therapy. Adequate respiratory and exercise training, as well as maintaining a positive mood, play a crucial role in enhancing patients' quality of life. (目的 调查慢性阻塞性肺疾病(COPD)患者居家肺康复训练和自我管理情况, 及居家肺康复训练和自我管理对患者生活质量的影响。方法 便利选取COPD患者作为研究对象, 运用"问卷星"在线问卷平台对81例COPD患者进行调查, 主要调查患者居家自我管理和肺康复训练的情况, 及自我管理和居家肺康复对患者生活质量的影响。结果 81例患者中, 46. 91%(38/81)的患者坚持呼吸训练(每周训练天数≥3 d), 61. 73%(50/81)的患者能坚持运动锻炼(每周锻炼天数≥3 d), 按医嘱服药的患者占75. 31%(61/81), 未进行家庭氧疗的患者占64. 20%(52/81)。COPD患者慢性阻塞性肺疾病评估测试(CAT)问卷总分为(20. 22 ± 7. 48)分, 属于中下水平。单因素分析显示, 年龄、学历、病程、有无工作、近1年因COPD而住院的次数、饮酒习惯、吸烟习惯、是否尝试戒烟、是否按时遵医嘱用药、是否家庭氧疗及持续氧疗时间、每周进行呼吸及运动训练天数会影响生活质量(P＜0. 01)。相关分析结果显示, 生活质量与饮酒频次、吸烟习惯、是否戒烟、是否按时遵医嘱用药、家庭氧疗及每天持续时间、每周呼吸训练天数具有相关性(P＜0. 01)。结论 居家肺康复的COPD患者应提高自我管理能力, 养成健康的生活习惯, 坚持科学家庭氧疗; 适当开展呼吸训练与运动训练; 保持愉快的心情, 对于提高生活质量具有重要的意义。)